PENGARUH CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia 2019-2020) - Maharani Syifa Dewi Azzahra; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2022)
This study aims to analyze the effect of corporate governance towards company’s financial distress as measured using the modified Altman Z-Score. The variables selected in this study are ownership structure (managerial ownership and institutional ownership), independent commissioners, audit committee expertise, and participation in the Corporate Governance Perception Index (CGPI) rating. The sample consists of banking companies listed on the Indonesia Stock Exchange in 2019-2020 using the purposive sampling method. Data analysis in this study used descriptive analysis and multiple linear regression. The results of the study confirm that managerial ownership, institutional ownership, independent commissioners, and audit committee expertise have a negative significant effect towards financial distress. Meanwhile, the Corporate Governance Perception Index (CGPI) has no effect towards financial distress.